(Cranfield DrivAer) CAD_Pack_1 Main Body - Francisco Soares, Renan; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Main Body CAD Pack (35% scaled-version), including:1. DrivAer_hp - Main_body (S):Main-body surface, with two cuttings for Rear-end and Diffuser CAD Pack.2. DrivAer_hp - Main_body (S) (diffuser lid):'Diffuser lid' surface, which matches the Main-body's Diffuser cutting in order to complete the Main-body, smooth underfloor version (S).CAD files available in IGS, STEP, STL, and Parasolid formats. All geometries are provided in [mm].Notation:(S) = [modified] Smooth Underfloor CAD designed and uploaded by:Renan F Soares - PhD in Aerospace Applied Aerodynamics Group Cranfield University, United Kingdom
Keywords: CAD; DrivAer; Automotive; Aerodynamics; Vehicle; Automotive Engineering not elsewhere classified; Aerodynamics (excl. Hypersonic Aerodynamics)